Rigidifying acyl carrier protein domain in iterative type I PKS CalE8 does not affect its function - Lim, Jackwee (2013)
Acyl carrier protein (ACP) domains shuttle acyl intermediates among the catalytic domains of multidomain type I fatty acid synthase and polyketide synthase (PKS) systems. It is believed that the unique function of ACPs is associated with their dynamic property, but it remains to be fully elucidated what type of protein dynamics is critical for the shuttling domain. Using NMR techniques, we found that the ACP domain of iterative type I PKS CalE8 from Micromonospora echinospora is highly dynamic on the millisecond-second timescale. Introduction of an interhelical disulfide linkage in the ACP domain suppresses the dynamics on the millisecond-second timescale and reduces the mobility on the picosecond-nanosecond timescale. We demonstrate that the full-length PKS is fully functional upon rigidification of the ACP domain, suggesting that although the flexibility of the disordered terminal linkers may be important for the function of the ACP domain, the internal dynamics of the helical regions is not critical for that function.